VD_FINDINFO Jug / 2021 / 44 vom 3. September 2020 - VD Tribunal cantonal (2020)
RESPONSABILITÉDROIT PÉNAL, ALARME, AFFECTION PSYCHIQUE, PEINE, REFORMATIO IN PEJUS | 12 CP, 128bis CP, 19 al. 1 CP, 19 al. 2 CP, 20 CP, 286 CP, 41 CP, 49 CP, 59 CP, 69 CP